Ocular Point-of-Care Ultrasound: Description of Intermediate Uveitis in an Adolescent Female. Issue 7 (July 2021) - Shah, Rahul; Rychwalski, Paul; Kurzweil, Ami; Tory, Heather; Chicaiza, Henry
Abstract : Abstract: Ocular point-of-care ultrasound has been used to assess for intraocular pathology, including retinal and vitreous detachment. We describe a pediatric patient whose initial point-of-care ultrasound examination appeared to be consistent with bilateral posterior vitreous detachment but who was ultimately diagnosed with intermediate uveitis. Abstract : Supplemental digital content is available in the text.